(untitled) (Research, Society and Development, 2020)
The objective of this study was to assess the correlation between the improvement of oral health-related quality of life (OHRQoL) and salivary cortisol levels on elders under oral prosthetic rehabilitation. Oral problems can influence both quality of life and salivary cortisol. However, it remains unknown if cortisol may act as a biomarker of OHRQoL in elders. Forty-one elderly participants answered a sociodemographic questionnaire and the Oral Health Impact Profile (OHIP-14) for OHRQoL. Participants were clinically evaluated and referred to a Public Geriatric Dental Clinic for prosthetic oral rehabilitation. Saliva samples were collected for cortisol quantification through ELISA, before (T1) and after (T2) prosthetic oral rehabilitation. A comparison between T1 and T2 was performed using the Wilcoxon test at 5% significance. The Standardized Response Mean (SRM) tested the responsiveness of OHIP-14. Twenty-seven patients with a mean age of 74±8.4 years old concluded the treatment. The OHIP-14 presented satisfactory responsiveness for the total score and in most domains (SRM>0.5). The total score of OHIP-14 and the domains Physical Pain, Physical and Psychological Disability were improved after the treatment (p<0.05). On the other hand, cortisol had a weak and non-significant correlation with OHIP-14 scores, except for the Functional Limitation domain (r=0.405, p<0.05). There was no difference between salivary cortisol levels between T1 and T2 (p>0.05). The salivary cortisol level did not present a direct association with OHRQoL in elders. On the other hand, the OHIP-14 questionnaire evidenced changes after oral rehabilitation, confirming the improvement of the elderly participants’ quality of life.